EFEKTIVITAS SERANGAN DWI CHAGI PADA SERANGAN HASIL POIN EVENT PERTANDINGAN ATLET NASIONAL DAN INTERNATIONAL TAEKWONDO - Puspita, Olivia; Sulastio, Agus; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to determine the effectiveness of the dwi chagi kickin scoring points in national and international taekwondo events. The research used asurvey method. The population for this study comprised 10 YouTube channel links,including 6 national event matches and 4 international event matches. The instrumentused was a checklist analysis of each dwi chagi kick. The data analysis technique usedwas percentage calculations. Based on the data analysis and discussion of the dwichagi kick in national and international taekwondo matches, athlete performance wasfairly consistent at both competition levels. The average score for successful kicks inboth events was 2.6, while unsuccessful kicks averaged 4.3. National events showed anaverage score per item of 6.16 out of a total of 37 points, and international eventsaveraged 8 out of 32 points. Therefore, it can be concluded that the dwi chagi kick isnot very effective in this study.Keywords: Dwi Chagi Kick, Taekwondo